Method of additional functions in stability theory for nonautonomous systems of differential equations - Kovalev, A.M.; Nespirnyy, V.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The method of additional functions in stability theory is expanded to nonautonomous systems. It has became possible due to a generalization of the method of invariant relations for this class of systems. The theorem of partial asymptotic stability is proved, and the illustrative example is considered.